A preliminary clinical report of transvaginal natural orifice transluminal endoscopic Sacrospinous Ligament Fixation in the treatment of moderate and severe pelvic organ prolapse - Qin, Zhenyue; Dong, Zhiyong; Tang, Huimin; Zhang, Shoufeng; Wang, Huihui; Bao, Mingyue; Wei, Weiwei; Shi, Ruxia; Chen, Jiming; Xia, Bairong (Frontiers in Surgery, 2022)
Study Objective To study the efficacy and safety of transvaginal natural orifice transluminal endoscopic sacrospinous ligament suspension in the treatment of moderate and severe pelvic organ prolapse. Design Patients who voluntarily accept this study were selected. Preoperative, comparison of POP-Q scores in June after surgery after surgery, by comparison results to determine the surgical effect.Setting and Patients Evaluate the clinical efficacy and safety by a retrospective analysis of the clinical data of the 18 patients with POP-Q grade Ⅲ-Ⅳ pelvic organ prolapse treated by the Department of Gynecology of Changzhou Second People's Hospital affiliated to Nanjing Medical University from April 2020 to November 2020, and their post-operation follow-ups.Interventions Patients with postoperative follow-up is not seen obviously has a relapse, not intervention measures.Measurements and Main Results Transvaginal single-hole laparoscopic ligament suspension was performed successfully, and anterior and posterior vaginal wall repair and/or vaginal hysterectomy were carried out as appropriate.Except for the total vaginal length (TVL), the P values of numerical analysis for all points before and 3 months after operation and 6 months after the operation were all < 0.05, being statistically significant.Conclusion This method is effective in the treatment of moderate and severe pelvic organ prolapse with few complications, but more cases and longer-term follow-up data are needed to determine the long-term effect of this procedure. For the selection of puncture sites, more anatomical data are needed to get more accurate result.